1994
DOI: 10.1111/j.1399-3054.1994.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Light quality beneath field‐grown maize, soybean and wheat canopies – red:far red variations

Abstract: Using artificial canopies, several authors have shown that horizontally propagated and overall propagated radiation beneath the canopy differ substantially in spectral distribution in the red (R) and far red (FR) wavelengths. Given the lack of information about light quality under real crop canopies, the R:FR ratio of vertical and horizontal radiation beneath field‐grown maize, soybean and wheat was monitored until leaf area index (LAI) reached 4, 2.5 and 6.9, respectively. A Li‐Cor 1800 spectroradiometer with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 27 publications
(13 reference statements)
1
34
0
Order By: Relevance
“…Thorough evaluation of the model for the strong sensitivity of to sky conditions would have required a precise characterization of sky conditions during measurements. However, measurements from the Wageningen 2004 experiment as well as data from Sattin et al (1994) and Sparkes et al (2006) did fall within the range of the simulated ratios. Moreover, simulation and measurements agreed closely in the cases where LAI > 5, that is when sky conditions had limited impact on ζ.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Thorough evaluation of the model for the strong sensitivity of to sky conditions would have required a precise characterization of sky conditions during measurements. However, measurements from the Wageningen 2004 experiment as well as data from Sattin et al (1994) and Sparkes et al (2006) did fall within the range of the simulated ratios. Moreover, simulation and measurements agreed closely in the cases where LAI > 5, that is when sky conditions had limited impact on ζ.…”
Section: Methodsmentioning
confidence: 67%
“…This explanation is supported by the fact that ζ ref was higher for the blue part of clear skies (1.7) than for the sun and overcast skies. Sattin et al (1994) also found that ζ ref was higher when measured with a 15° FOV than with a hemispherical FOV. The difference in ζ ref among clear skies, overcast skies, and sun also influenced the downward ζ inside the canopy when the degree of scattering was low, i.e.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It should be noted that, in natural shading scenarios, light spectrum differs the non-shading (Sattin et al 1994). The variations in spectral quality also affect crop physiological processes, growth and yield (Causin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Light interception through the canopy is key to maintaining high photosynthetic capacity in plants as increased penetration of light through the canopy is responsible for increased dry matter production on whole (Sinclair, 1998) and assimilate partitioning to the ear (Hammer et al, 2009), contributing toward higher grain yields (Dwyer et al, 1991;Stewart et al, 2003). Competition for light can occur before canopy shading begins from neighboring plants (Sattin et al, 1994). As plants are increasingly crowded at high plant density, the canopy begins to self-shade, which results in decreased light penetration into the canopy and leads to decreased grain yield (Duncan, 1971;Hammer et al, 2009;Stewart et al, 2003).…”
Section: Photosynthetic Capacitymentioning
confidence: 99%